Q. 123.9( 21 Votes )

Polynomials <span

Answer :

Put x = 3 in the first polynomial:

b× (3)2 + 3 + 5 = m


9b + 8 = m ………………………………….. (i)


Put x = 3 in the second polynomial


b× (3)3 -2× 3 + 5 = n


27b -6 + 5 = n


27b -1 = n …………………………………. (ii)


Equation (i) – (ii)


m –n = 9b + 8 – (27b -1)


but m-n = 0


9b + 8 -27b + 1 = 0


-18b + 9 = 0


18b = 9


b = 9/18


b = 1/2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Divide polynomialMHB - Math Part-I

For which the valMHB - Math Part-I

If x-2 and x – 1/MHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

Divide the first MHB - Math Part-I

By using factor tMHB - Math Part-I

Show that m-1 is MHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

<span lang="EN-USMHB - Math Part-I

Use factor theoreMHB - Math Part-I